Nonlinear Time-Dependent Analysis of the Load-Bearing Capacity of a Single Permanent Shotcrete Lining at the Brenner Base Tunnel. Issue 4 (1st October 2020) - Neuner, Matthias; Dummer, Alexander; Schreter, Magdalena; Hofstetter, Günter; Cordes, Tobias; Bergmeister, Konrad
Abstract: The Brenner Base Tunnel (BBT), a 64 km long railway tunnel between Austria and Italy, is under construction at the time of writing. The complete tunnel system of the BBT will comprise railway tunnels as well as exploration, emergency, ventilation and access tunnels. The latter are tunnels with generally lower requirements on the serviceability, watertightness, durability, surface quality or availability. In some cases, a single permanent shotcrete lining can fulfill the reduced requirements and offers a very economic tunnel design. Realistic assessment of the load-bearing capacity of shotcrete linings is particularly required for early and large deformations in deep tunnels. This is the motivation for a more sophisticated approach to the back-analysis of a permanent shotcrete lining of a single lined rescue tunnel of the BBT. Thus, a detailed finite element model is developed for analyzing the bearing capacity of the permanent shotcrete lining on the basis of an advanced constitutive model considering the time-dependent and nonlinear material behavior of shotcrete. The material model represents the time-dependent evolution of material properties due to hydration of shotcrete, hardening and softening material behavior, the latter resulting in cracking or crushing of shotcrete, creep and shrinkage. In the finite element model, the time-dependent construction process of the drill-and-blast method for tunnels driven by partial face excavation is considered. The material parameters for the shotcrete model were calibrated based on an experimental program, performed with specimens sampled directly on the construction site of the BBT.